Optimization of Follow-Up of Education Financing in Creating Quality Educational Units - H. Soro, Suharyanto; Janah, Nur; Nurhasanah, Teti (Global Education Journal, 2025)
Optimization act carry on financing education become crucial in increase quality unit education, especially in the era of reform and digitalization. Action carry on financing education is one of problem faced by one education Because related with utilization transparent budget as well as accountable. Research This use framework theory management education based on quality as runway analysis. Research This aiming For describe and analyze about optimization act carry on financing education to create unit good quality education from aspect implementation and also achievement results learning . The research method used is approach studies case with locus research at Cangkuang State Elementary School (SDN). Researchers use method data collection namely observation, interviews and documents. Research results show that act carry on structured and achievement - oriented financing learning impact positive to program planning, efficiency use of funds, and involvement stakeholders interests . In addition, participation active from head schools , teachers and committees school in the process of taking decision financing proven capable increase accountability and quality service education. Research conclusion is optimization act carry on financing education done through participatory planning, monitoring sustainable, as well as transparent reporting as effort strategic in create unit superior and sustainable education.